A control strategy for cylinder deactivation. (October 2020) - Ritzmann, Johannes; Zsiga, Norbert; Peterhans, Christian; Onder, Christopher
Abstract: Cylinder deactivation is an effective measure to reduce the fuel consumption of internal combustion engines. This paper presents a control strategy for the cylinder deactivation (CDA) process and the cylinder reactivation (CRA) process, based on the inversion of a control-oriented discrete-event model. The focus of this paper lies on quantity-controlled stoichiometrically-operated engines with different layouts. Nevertheless, the main results are transferable to other engines, including quality-controlled engines. Two major aspects of CDA and CRA are considered in detail in this paper. The first aspect is the cycle-averaged torque during the CDA and CRA. Due to the reciprocating behaviour of the engine, an unavoidable discontinuity in the cycle-averaged torque is identified, irrespective of the type of engine. The amplitude of this torque ripple depends on the duration of the CDA or CRA and can be quantified a priori. A trade-off between the torque ripple amplitude and the CDA or CRA duration is identified. The second aspect is the amount of fuel consumed during the CDA and CRA. It is shown that to achieve a CDA or CRA with a limited torque ripple amplitude, some combustion cycles at unfavourable low-load conditions must occur. For example, ignition retardation might be used resulting in a significant portion of the fuel energy being lost. As a result an increase in the amount of fuel consumed during the CDA or CRA compared to that of continued operation in activated cylinder mode may arise. The conducted investigations show that this increase in fuel consumption is compensated after a few seconds of operation in the more fuel-efficient deactivated cylinder mode.